Community-Based Learning for Sustainable and Reverse Logistics: Building a Cross-Border Practice Community - Nasution, Nursery Alfaridi S; Octaviani, Reni Dian; Sari, Mustika; Anashkina, Nataliia; Firdaus, Muhammad Iqbal; Thabah, Asep Ali (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
The global logistics industry faces increasing challenges related to environmental sustainability and resource management. Sustainable logistics and reverse logistics are essential concepts that help reduce environmental impact, enhance operational efficiency, and support the circular economy. However, awareness and understanding of these concepts among emerging logistics practitioners and community members remain limited. This study presents the outcomes of an online community engagement program aimed at establishing a logistics learning community focused on sustainable and reverse logistics. The program involved collaborative activities between facilitators from Ural State University of Railway Transport, Russia, and participants representing the logistics practice community. Learning outcomes were measured through pre- and post-tests, showing a significant improvement in the average score from 41.1 to 87.4, demonstrating the program’s success in building practical knowledge and application of sustainable logistics. To enhance the real-world application of knowledge, the program integrated small-group discussions where participants collaboratively worked on local case studies to apply the principles learned. This initiative offers valuable insights for designing future cross-border educational outreach and international academic collaboration using digital platforms.